2015
DOI: 10.1128/mbio.00493-15
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in the Collaborative Cross Model Recapitulates Human West Nile Virus Disease Outcomes

Abstract: West Nile virus (WNV) is an emerging neuroinvasive flavivirus that now causes significant morbidity and mortality worldwide. The innate and adaptive immune responses to WNV infection have been well studied in C57BL/6J inbred mice, but this model lacks the variations in susceptibility, immunity, and outcome to WNV infection that are observed in humans, thus limiting its usefulness to understand the mechanisms of WNV infection and immunity dynamics. To build a model of WNV infection that captures human infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
116
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(116 citation statements)
references
References 44 publications
0
116
0
Order By: Relevance
“…Notably, however, half of the mice surviving past d13 p.i. displayed sustained weight loss that was distinct from B6 mice (Fig 1A), as well as from the 100+ RIX lines screened [17]. Due to this novel and unique sustained weight loss following infection, we examined the viral burden within the CNS to determine if virus also persisted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, however, half of the mice surviving past d13 p.i. displayed sustained weight loss that was distinct from B6 mice (Fig 1A), as well as from the 100+ RIX lines screened [17]. Due to this novel and unique sustained weight loss following infection, we examined the viral burden within the CNS to determine if virus also persisted.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that the CC can be used as a resource to model WNV infection in humans such that infection and comparison of CC mouse lines improves upon inbred mouse models to better capture the diversity of WNV infection outcomes observed across the genetically diverse human population [17]. Here, we further characterize the RIX line CC032/GeniUnc crossed to CC013/GeniUnc (hereafter CC(032x013)F1)), which serves as a mouse model of chronic WNV infection.…”
Section: Introductionmentioning
confidence: 99%
“…West Nile virus TX-2002-HC (WN-TX) was propagated using previously described methods [4]. Viral stocks were generated using supernatants collected from infected vero cell lines and stored at 80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Variability in disease outcomes has been reported regularly for WNV infections in humans and certain mouse strains (Graham et al, 2015;Petersen et al, 2013). Particularly relevant in an Australian context, variable end-point disease outcomes have been reported for other Australian WNV strains of intermediate virulence in the Swiss white mouse model (Bingham et al, 2014).…”
Section: Astrocytic and Microglial Activationmentioning
confidence: 98%